Pengaruh Return On Asset, Current Ratio dan Firm Size Terhadap Nilai Perusahaan Pada Perusahaan Sub Sektor Tekstil dan Garmen di Bursa Efek Indonesia (BEI) - Amani, Tatik; Haidiputri, Trivosa Aprilia Novadiani; Rahmawati, Siti Oktaviani Dwi (Jurnal PenKoMi : Kajian Pendidikan dan Ekonomi, 2024)
This research aims to determine the influence of Return On Assets, Current Ratio and Firm Size on Company Value in Textile and Garment Sub-Sector Companies on the Indonesia Stock Exchange (BEI). The type of research used is quantitative research. Data collection techniques by means of documentation. The population in this study were 23 textile and garment companies listed on the Indonesia Stock Exchange (BEI) during 2020-2022. The sample in this study used 20 companies with techniques sampling purposive. This research data uses secondary data. The data analysis techniques used are descriptive statistical analysis, classical assumption testing, multiple linear regression analysis, coefficient of determination (R2) analysis and hypothesis testing. The research results show that return on asset and current ratio partial effect on the value of the company. Meanwhile, firm size has a negative and significant effect on company value. Return on asset, current ratio and firm size have a simultaneous effect on company value. Return on assets has a dominant influence on company value.